2020
DOI: 10.1177/000313482008600106
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Withdrawal of Life-Sustaining Treatment in Severe Traumatic Brain Injury

Abstract: Studies demonstrate a significant variation in decision-making regarding withdrawal of life-sustaining treatment (WLST) practices for patients with severe traumatic brain injury (TBI). We investigated risk factors associated with WLST in severe TBI. We hypothesized age ≥65 years would be an independent risk factor. In addition, we compared survivors with patients who died in hospital after WLST to identify potential factors associated with in-hospital mortality. The Trauma Quality Improvement Program (2010–201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…[8][9][10] Few studies have investigated WLST trends in severe TBI. A study performed by Gambhir et al 11 identified patient-related and injury-related WLST factors, including age and race. However, noninjury factors for WLST in severe TBI have not been well characterized.…”
mentioning
confidence: 99%
“…[8][9][10] Few studies have investigated WLST trends in severe TBI. A study performed by Gambhir et al 11 identified patient-related and injury-related WLST factors, including age and race. However, noninjury factors for WLST in severe TBI have not been well characterized.…”
mentioning
confidence: 99%
“…This finding is consistent with previous reports in Europe and America. 2 , 4 , 5 , 6 , 7 , 8 , 10 , 11 , 12 …”
Section: Discussionmentioning
confidence: 99%
“…Older age was shown to be an independent factor related to the choice of WLST in American, Canadian, French, and Dutch studies on severe TBI. 4 , 5 , 6 , 7 , 8 Previous reports have found that patients with WLST have a higher frequency of acute subdural hematoma (ASDH) than those without WLST in severe TBI settings. 6 However, there is little evidence on the factors influencing the decision to withdraw or continue LSTs in the setting of severe TBI in Japanese institutions.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, it can also prevent the generation of oxygen free radicals, improve the microcirculation in patients, and reduce the damage of tissues and organs under inflammatory and ischemic conditions so as to increase the tolerance of the liver to hypoxia [ 18 20 ]. Currently, ulinastatin has been widely used in the treatment of severe traumatic craniocerebral injury and severe pancreatitis for its good therapeutic effect and high safety [ 21 , 22 ]. Xingnaojing is made from Angong Niuhuang Pills which has the effects of cooling blood and detoxicating, clearing away heat and toxic material and eliminating phlegm for resuscitation.…”
Section: Discussionmentioning
confidence: 99%